PULMONARY ARTERIOVENOUS MALFORMATION: STILL A SURGICAL CONSIDERATION - S. Shahidnoorai M.Rahbar (Acta Medica Iranica, 1998)
Pulmonary arteriovenous malformations are rare clinical entities thai are associated with right to left shunts, and are often clinically presented by the triad of dyspnea, cyanosis, and digital clubbing. Currently, transcatheter embolization of fistula is gaining increasing popularity as the superior therapeutic option. In certain situations, however, surgery is preferred. Two cases of direct pulmonary artery ■ left atrial fistulas are described who, were treated simply by surgery with no recurrence.